Pattern detection and design rationale traceability: an integrated approach to software design quality. Issue 4 (1st August 2019) - Aladib, Loay; Lee, Sai Peck
Abstract : Design rationale is the synthesis of the structure that is consistent with the model of an artefact, decisions, alternative approaches, and the reasoning behind it. Hence, bypassing it will result in poor quality systems engineering. Ambiguous representation of design rationale goals is just one of the many limitations that contributes to the intricacy of design patterns, thereby this research aims to introduce an approach to support the structuring, evaluation, and analysis of design patterns. The authors have proposed a method and implemented an associated tool with a mechanism that validates the class relationships and properties of design patterns comprehensively, resulting in a reliable pattern detection result. The preliminary results of the proposed research show that although detection and evaluation of a design pattern require some overhead using the approach, it does contribute to the confidence of the developers and gives affirmation that the design pattern implemented in the source code achieves its defined rationale goals based on the gang of four definition of design patterns through the reliable pattern detection output and straightforward evaluation result. The conclusion could be drawn that through the proposed approach, the preliminary result resolves the intricacy of design rationale traceability while achieving software quality is permissible.